Angioimmunoblastic T-cell lymphoma: treatment strategies and prognostic factors from a retrospective multicenter study in China. Issue 5 (16th April 2022) - Zhang, Chen; Mi, Lan; Wu, Meng; Liu, Weiping; Ma, Hongmei; Ren, Jianxin; Zhao, Linjun; Wang, Xiaopei; Song, Yuqin; Zhu, Jun
Abstract: Angioimmunoblastic T-cell lymphoma (AITL) is a unique sub-type of peripheral T-cell lymphoma (PTCL). We aimed to evaluate treatment programs and prognostic factors of 121 newly diagnosed patients with AITL in China from January 2001 to December 2018. The median age was 58 years with male predominance. Bone marrow involvement appeared in only 8.3% of patients, which was different from the previously published literature. The 5-year progression-free survival (PFS) and 5-year overall survival (OS) were 29.7% and 44.0%, respectively. Univariate and multivariate analyses showed that involvement of >5 nodal areas, age and Beta-2 microglubulin were highly predictive of OS but only the involvement of fewer than five nodal areas was significant for PFS. We identified a novel prognostic model including the three factors that may be applied in clinical practice and offer an alternative to IPI and PIT.